Penyuluhan Tentang Banjir Pada Masyarakat Dan Pemuda di Kelurahan Mandalika Sandubaya Kota Mataram - Negara, I Dewa Gede Jaya; Karyawan, I Dewa Made Alit; Supriyadi, Anid; Mahendra, Made; Saidah, Humairo; Merdana, I Nyoman; Sulistiyono, Heri; Yasa, I Wayan; Suparjo, Suparjo; Suroso, Agus (Universitas Mataram, 2024)
, because there are still many residents who do not understand what floods are and what to do when experiencing floods. To provide awareness about floods, education about floods must be carried out for children and the elderly so that it occurs. similarities in perception and knowledge about this matter, especially for city residents in upstream areas such as in Mandalika Village. Education about floods is carried out in several stages, including the initial survey stage, coordination, discussion, question and answer activities and evaluation. The counseling material provided includes perceptions about floods, factors that cause floods, ways to avoid and reduce the occurrence of floods and the infrastructure needed to anticipate floods. During the outreach process, discussion and question and answer sessions were also provided, to increase participants' understanding of floods. The result of the service that has been carried out is being able to provide counseling to the community, both young people and parents, totaling 25 representatives who attended, including the management of Banjar Sedana Ayu. Participants have gained knowledge about floods and have understood the phenomenon of flooding and ways to avoid it after a question and answer session at the end of the outreach activity. By having the participants at the location of this trial, some of the people in the Mandalika sub-district already understand how floods occur and are expected to be able to deal with them if they happen.